Reluctance of Acehnese youth to use Acehnese - Teuku Muhammad Ridha Al-Auwal (Universitas Syiah Kuala, 2017)
This study was aimed at finding the main factors causing Acehnese youth to be reluctant to use their Acehnese language within their groups and in daily life and also at finding out their attitudes towards the Acehnese language. The study adopted a case study approach using semi-structured interviews to obtain data. Ten (10) participants, who were members of the Students Union of Syiah Kuala University, the so-called PEMA Unsyiah, who were considered representative of all the students, took part in this study. The findings revealed that negative attitudes to their Acehnese language have mushroomed amongst Acehnese youth today. Acehnese youth are now accustomed to using Indonesian instead of Acehnese language in their everyday life due to several reasons, namely: Indonesian seems more modern (showing the person to be upper- class), they feel spoken Acehnese sounds ‘harsh’ and ‘weird’, Indonesian is predominant on campus now, Indonesian seems more prestigious and ‘cooler’, Indonesian can be used to neutralize the differences between different Acehnese dialects and languages, Indonesian is more convenient whilst Acehnese is more difficult, Acehnese is mainly used for making jokes, humour and puns, Indonesian is more reasonable and convenient to communicate with the opposite sex, if communication is already running in Indonesian, it is difficult to switch it to Acehnese, and finally, Indonesian is easier and more convenient to use to greet new friends.